Enhancing Safety in Reconstructive Microsurgery Using Intraoperative Indocyanine Green Angiography - Ludolph, Ingo; Horch, Raymund E.; Arkudas, Andreas; Schmitz, Marweh (Frontiers in Surgery, 2019)
Intraoperative assessing and postoperative monitoring of the viability of free flaps is of high relevance in reconstructive microsurgery. Today different methods for the evaluation of tissue perfusion are known. Indocyanine Green angiography is an emerging technique among plastic surgeons with a broad scope of applications especially in microsurgical free flap transfer. We demonstrate the value and clinical application of this technique based on representative selected cases where Indocyanine Green angiography was used in complex microsurgical free flap transfers from different anatomic donor sites during the operation. Hereby perforator selection, flap tailoring, changes of blood flow and patency of anastomoses were judged and decision making was based on the angiographic findings. This method has proven to be valid, reproducible and easy to use. The application is not limited to the evaluation of skin perfusion, but is also applicable to muscle tissue or chimeric or composite flaps. Reliable judgement is especially given for the extent of arterially perfused tissue following complete flap dissection. Moreover this real-time angiography revealed a high sensitivity for the detection of poorly perfused flap areas, thus supporting the conventional clinical judgement and reducing complications. In summary Indocyanine Green angiography has the potential to reduce flap related complications and to contribute to enhancing and extending the possibilities of free flap surgery.